PGD2/PTGDR2 Signal Affects the Viability, Invasion, Apoptosis, and Stemness of Gastric Cancer Stem Cells and Prevents the Progression of Gastric Cancer - Zhang, Qiang; Wang, Feifan; Huang, Yan; Gao, Peiyao; Wang, Na; Tian, Hengjin; Chen, Amin; Li, Yuyun; Wang, Fengchao (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: Prostaglandin D2 (PGD2) has been shown to restrict the occurrence and development of multiple cancers; nevertheless, its underlying molecular mechanism has not been fully elucidated. The present study investigated the effect of PGD2 on the biological function of the enriched gastric cancer stem cells (GCSCs), as well as its underlying molecular mechanism, to provide a theoretical basis and potential therapeutic drugs for gastric cancer (GC) treatment. Methods: The plasma PGD2 levels were detected by Enzyme-linked immunosorbent assay (ELISA). Silencing of lipocalin prostaglandin D synthetases (L-PTGDS) and prostaglandin D2 receptor 2 (PTGDR2) was carried out in GCSCs from SGC-7901 and HGC-27 cell lines. Cell Counting Kit-8, transwell, flow cytometry, and western blotting assays were used to determine cell viability, invasion, apoptosis, and stemness of GCSCs. In vivo xenograft models were used to assess tumor growth. Results: Clinically, it was found that the plasma PGD2 level decreased significantly in patients with GC. PGD2 suppressed viability, invasion, and stemness and increased the apoptosis of GCSCs. Downregulating L-PTGDS and PTGDR2 promoted viability, invasion, and stemness and reduced the apoptosis of GCSCs. Moreover, the inhibition of GCSCs induced by PGD2 was eliminated by downregulating the expression of PTGDR2. The results of in vivo experiments were consistent with those of in vitro experiments. Conclusion: Our data suggest that PGD2 may be an important marker and potential therapeutic target in the clinical management of GC. L-PTGDS/PTGDR2 may be one of the critical targets for GC therapy. The PGD2/PTGDR2 signal affects the viability, invasion, apoptosis, and stemness of GCSCs and prevents the progression of GC.
Keywords: prostaglandin D synthetases